Design and Assessment of Species-Level qPCR Primers Targeting Comammox - Beach, Natalie K.; Noguera, Daniel R. (Frontiers in Microbiology, 2019)
Published PCR primers targeting the ammonia monooxygenase gene (amoA) were applied to samples from activated sludge systems operated with low dissolved oxygen (DO) to quantify total and clade-level Nitrospira that perform complete ammonium oxidation (comammox); however, we found these existing primers resulted in significant artifact-associated non-target amplification. This not only overestimated comammox amoA copies but also resulted in numerous false positive detections in the environmental samples tested, as confirmed by gel electrophoresis. Therefore, instead of attempting to quantify comammox diversity, we focused on accurately quantifying the candidate comammox species. We designed specific and sensitive primers targeting 3 candidate species: Candidatus (Ca.) Nitrospira nitrosa, Ca. N. inopinata, and Ca. N. nitrificans. The primers were tested with amoA templates of these candidate species and used to quantify comammox at the species level in low DO activated sludge systems. We found that comammox related to Ca. N. nitrosa were present and abundant in the majority of samples from low DO bioreactors and were not detected in samples from a high DO system. In addition, the greatest abundance of Ca. N. nitrosa was found in bioreactors operated with a long solids retention time. Ca. N. inopinata and Ca. N. nitrificans were only detected sporadically in these samples, indicating a minor role of these comammox in nitrification under low DO conditions.